(untitled) (Nexo Revista Científica, 2020)
The study area is located 5.5 km north-east of Kamo County and 30 km north-east of Meymeh, Isfahan. Kamo Index comprises an anticline with a northwest-southeast trend, the outcrop of which consists of siltstone-sandstone and Jurassic shale rocks that lie along a cretaceous unit. Based on field studies as well as petrographic and geochemical investigations, mineral assemblages and minerals in the area include chalcopyrite, pyrite, marcasite, and magnetite as primary ores and malachite, bornite, covellite, chalcocite, hematite, goethite, and hydrous iron oxides as secondary ores. The secondary ores have been formed by oxidation and biogenic processes. The primary textures are granular, disseminated, vein-shaped, and layered and the secondary textures are boxed and martitized, shear zones, replacements, and veins. Tectonic, metamorphic, and oxidation factors are involved in the formation of these textures. Due to tectonic activity in this area and the presence of faults, replacement, vein, and shear textures, which have developed after mineralization, are observed. Among alterations, hematite, propylitic, sericitic, limonitic, and kaolinitic are highly prevalent and they are important in the formation of iron deposits. The sub-alkaline granitoids of the region are related to the continental subduction-zone orogenic series. Studies on the decomposed iron samples from Kamo show that most of the samples are in the sub-alkaline series and the chemical and mineralogical composition of the magma derived from this series is calc-alkaline with a large amount of iron. According to mineralogical, lithological, and geochemical evidence and based on isotopic results, Kamo deposit is a skarn-type deposit.